Pengelolaan Arsip Dalam Meningkatkan Tertib Administrasi Di Uin Sayyid Ali Rahmatullah Tulungagung - Ameiliya, Amy; Handayani, Nurul Setyawati (Ilmu Informasi Perpustakaan dan Kearsipan, 2023)
UIN Sayyid Ali Rahmatullah Tulungagung encounters obstacles in its archival management due to a shortage of human resources. The objective of this research is to illustrate how the management of archives can be improved to promote better administrative structure at UIN Sayyid Ali Rahmatullah Tulungagung and identify the challenges it faces. This study utilizes a descriptive approach to qualitative research methodology. Data collection involves observation, interviews with one archivist and two archive users, and documentation. The validity of the data is ensured through the triangulation technique. The research findings reveal that archive management at UIN Sayyid Ali Rahmatullah Tulungagung operates effectively, adopting a decentralized approach where each faculty assumes responsibility for receiving, recording, distributing, and retrieving archives. The implementation of digital systems such as Sistem Informasi Tata Naskah Dinas (Si-TANDA) has made a significant contribution to maintaining well-organized administration. In the future, UIN Sayyid Ali Rahmatullah Tulungagung needs to prioritize the augmentation of its human resources.